Revitalization of Syingiran as A Strengthening of Sociality and Spirituality of Rural Communities: The Existence of Oral Literature - Ngarifah, Imroatul; Basri, Hasan; Fakhrurrazi, Fakhrurrazi (Sosial Budaya, 2023)
Syingir or song has been known since the era before the arrival of Islam in Indonesia. After Islam came, Syingir was used as a medium for preaching which was echoed in mosques and majlis ta'lim. However, along with the development of the times, Syingir is considered old-fashioned and is rarely sung, especially in urban communities. But some rural communities still chant it. The purpose of this study was to find out the forms of Syingir sung by Rejosari villagers, and the social values contained in the activities of Syingiran Rejosari villagers, Syingir as a strengthening of the spirituality of rural communities. This research is qualitative-based field research. The main object of this research is the Syingiran activities of the Rejosari village community and the chants that are sung. The results of this study are (1) the form of the revitalization of Syingir in Rejosari village is by making efforts to replace, preserve, inherit, and manage Syingiran activities, (2) the social values contained in Syingiran activities are the value of togetherness, the value of patience, the value of leadership, and Amar makruf nahi munkar, (3) as a strengthening of the spirituality of the rural community of the Syingir-Syingir teaches people to always remember God and read the Qur'an, pray for their predecessor, keep holding prayers under any circumstances, always remember death, and always do kindness.